2019
DOI: 10.1038/s41467-019-10294-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered respiratory virome and serum cytokine profile associated with recurrent respiratory tract infections in children

Abstract: Recurrent acute respiratory tract infections (ARTIs) affect a large population, yet the specific decisive factors are largely unknown. Here we study a population of 4407 children diagnosed with ARTI, comparing respiratory virome and serum cytokine profiles associated with multiple ARTIs and single ARTI during a six-year period. The relative abundance of Propionibacterium phages is significantly elevated in multiple ARTIs compared to single ARTI group. Serum levels of TIMP-1 and PDGF-BB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 75 publications
2
41
1
1
Order By: Relevance
“…Historically, viruses have been viewed as threatening because they were best known for causing disease. While their full role in human health is still mostly unknown [26,27], we are beginning to understand the associations between the enteric and respiratory virome and acute and chronic human diseases [27][28][29][30], and a recent study showed that bacteriophages modulate bacteria communities in the gut [31]. The majority of viruses and virusderived genetic elements appear to be benign; some may even be essential for good health if the hygiene hypothesis [32] applies to viruses as well as bacteria.…”
Section: Healthy Viromementioning
confidence: 99%
“…Historically, viruses have been viewed as threatening because they were best known for causing disease. While their full role in human health is still mostly unknown [26,27], we are beginning to understand the associations between the enteric and respiratory virome and acute and chronic human diseases [27][28][29][30], and a recent study showed that bacteriophages modulate bacteria communities in the gut [31]. The majority of viruses and virusderived genetic elements appear to be benign; some may even be essential for good health if the hygiene hypothesis [32] applies to viruses as well as bacteria.…”
Section: Healthy Viromementioning
confidence: 99%
“…Bacteriophages are active regulators of bacterial populations [50][51][52] and changes in phage composition or diversity have been linked to various diseases including Inflammatory Bowel disease, Parkinson's disease and Type 1 Diabetes 53 . Moreover, bacteriophages can protect the epithelium from bacterial infections in a mucus-dependent manner, or can modulate the innate and adaptive arms providing non-host immunity 37,52,[54][55][56][57][58] . In addition to reduced diversity and frequency of phage occurrence in asthmatics, the asthmatic metacommunity was characterised by a low number of phage-bacteria pairs, suggesting limited predator-prey ecological interactions [59][60][61][62] .…”
Section: Dysbiotic Structure Of the Asthmatic Viromementioning
confidence: 99%
“…Most importantly, our knowledge on prokaryotic viruses infecting bacteria (bacteriophages or phages) is extremely limited, even though they are the most straightforward link between viruses and bacteria in the respiratory system 35 . Only a handful of studies have investigated the respiratory prokaryotic virome 36,37 and to our knowledge none in asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory tract infection (ARTI) is a leading cause of hospitalization, morbidity, and mortality in children in pediatrics throughout the world . Many pathogens including bacteria, virus, mycoplasma , chlamydia, and fungi can result in ARTI; virus (such as human respiratory syncytial virus [HRSV], human rhinovirus [HRV], influenza virus [IFV], human coronavirus [HCOV], and human adenovirus [HADV]) has been identified as a major cause in ARTI in children .…”
Section: Introductionmentioning
confidence: 99%